Ruggedizing Printed Circuit Boards Using a Wideband Dynamic Absorber - V.C. Ho; A.M. Veprik; V.I. Babitsky (Shock and Vibration)
The existing approaches to ruggedizing inherently fragile and sensitive critical components of electronic equipment such as printed circuit boards (PCB) for use in hostile industrial and military environment are either insufficient or expensive. This paper addresses a novel approach towards ruggedizing commercial-off-the-shelf PCBs using a miniature wideband dynamic absorber. The optimisation technique used relies on the experimentally measured vibration spectra and complex receptance of the original PCB.